Histopathological Findings of Acute Kidney Injury in Pediatric Coronavirus Disease-19 Patients: A Systematic Review - Muhammad Tidar Abiyu Amiruddin; Anny Setijo Rahaju; Risky Vitria Prasetyo; Citrawati Dyah Kencono Wungu (Wolters Kluwer - Medknow Publications, 2023)
Introduction: Acute kidney injury (AKI) is a complication of coronavirus disease-19 (COVID-19), and the pathophysiology of AKI in COVID-19 could be determined as multifactorial. The exact prevalence of AKI in COVID-19 patients is growing over time. Due to the difficulties, kidney biopsy is performed in a small minority of AKI patients infected with COVID-19. Materials and Methods: This systematic review was conducted adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Keywords used in this study were: "acute kidney injury" AND "histology" AND "children" OR "pediatric" AND "COVID" and searched from databases such as PubMed/MEDLINE, ScienceDirect, Scopus, and SpringerLink. After obtaining eligible studies, the articles were assessed with the Joanna Briggs Institute checklist for case report. Results: Seven eligible studies were obtained and assessed. The clinical data showed variable initial symptoms; however, fever, abdominal pain, and respiratory disturbances were shown to be the common comorbidities aligning with the pattern of the COVID-19 symptoms themselves. In the histopathological report from the data, 88.8% (8/9) of patients were found with acute tubular necrosis (ATN). The second-most commonly found pathological data from the histology report were congestion and thrombosis; both of which were present in 55.5% (5/9) of patients each, followed by focal segmental glomerulosclerosis in 80% (4/5) of patients. It should be noted that more than one pathology is found in each patient. Conclusion: The findings of the review indicate that ATN followed by congestion and thrombosis are the most common histopathological manifestations in pediatric AKI patients due to COVID-19.